The webinar on the role of media in a global pandemic: how the media is changing the way you think? - Wan Mohd Ghazali, Wan Norshira (2020)
The main idea for this webinar is to explain, explore and discuss the role of media in getting our society informed (especially with getting correct information) during emergency period a.k.a pandemic era of Covid-19 and how a public figure/famous people can teach us lessons/play a role in adapting to the 'new normal'.